Treatment-Related Coronary Disorders of Fluoropyrimidine Administration: A Systematic Review and Meta-Analysis - Lu, Yajie; Deng, Shizhou; Dou, Qiongyi; Pan, Wei; Liu, Qingqing; Ji, Hongchen; Wang, Xiaowen; Zhang, Hong-Mei (Frontiers in Pharmacology, 2022)
Background: Coronary disorders are recognized as the most common manifestation of fluoropyrimidine-related cardiotoxicity in clinical practice. However, there are limited and conflicting data on the incidence and profiles of fluoropyrimidine-related coronary disorders. We aimed to systematically assess the incidence of all-grade and grade 3 or higher fluoropyrimidine-related coronary disorders, and further explore the factors that influence its occurrence. Methods: Studies reporting the fluoropyrimidine-related coronary disorders were retrieved from a systematic search of English literature in the PubMed, Web of Science, Medline, and Cochrane database from Jan 1, 2001, to Jan 1, 2022. The NIH assessment tool was used to evaluate the quality of each study. The data of basic study characteristics, treatment details, and results of coronary toxicities were extracted. According to the results of the heterogeneity test, a random-effect model or fixed-effect model was selected for the pooled analysis of the incidence of adverse coronary events. Subgroup analysis was conducted to further explore the risks influencing the occurrence of fluoropyrimidine-related coronary disorders. The stability and publication bias of our results were evaluated by sensitivity analysis and Egger test, respectively. Results: A total of 63 studies were finally included in our pooled analysis, involving 25577 patients. The pooled cumulative incidence of all-grade and grade 3 or higher coronary disorders was 2.75% and 1.00%, respectively. The coronary disorders were most reported as myocardial ischemia (1.28%) and angina/chest pain (1.1%). Subgroup analysis revealed that studies in the female-only population seemed to have a lower incidence of fluoropyrimidine-related coronary disorders. The occurrence of adverse coronary events varied among different tumor types. Patients with esophageal cancer have the highest coronary toxicity (6.32%), while those with breast cancer have a relatively lower incidence (0.5%). Coronary disorders induced by 5-FU monotherapy are more frequent than that induced by capecitabine (3.31% vs. 1.21%, p<0.01). Fluoropyrimidine combination therapy, whether combined with other chemotherapy drugs, targeted therapy drugs, or radiotherapy, significantly increased the incidence of coronary complications (p<0.01). Conclusions: This meta-analysis has defined the incidence of fluoropyrimidine-related coronary disorders and depicted its epidemiological profiles for the first time, which may provide a reference for clinical practice in cancer management.